2019
DOI: 10.1177/1932296818822998
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and Behavior Change Techniques in Diabetes Self-Management Apps

Abstract: Background: Diabetes management apps may have positive effects on diabetes self-management. It remains unclear, however, which app features are particularly effective and encourage sustained app usage. Behavior change techniques (BCTs) and gamification are promising approaches to improve user engagement. However, little is known about the frequency BCTs and gamification techniques (GTs) are actually used. This app review aims to provide an overview of BCTs and GTs in current diabetes management apps. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…Interestingly, program exposure (an average of 18 appointments with Laura ) is very similar to the TLC diabetes program previously developed and evaluated by our team in Australia [ 34 ]; however, the program is more intensive than a human-delivered program that is widely available in Australia (a maximum of eight face-to-face group sessions per calendar year) [ 35 ]. Some gamification elements and human-like characteristics were utilized in the MDC program design, as suggested by previous studies [ 36 ]. The recently published and separate evaluation from MDC users demonstrated that these techniques did increase users’ engagement with the program but were insufficient to ensure engagement among all users [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, program exposure (an average of 18 appointments with Laura ) is very similar to the TLC diabetes program previously developed and evaluated by our team in Australia [ 34 ]; however, the program is more intensive than a human-delivered program that is widely available in Australia (a maximum of eight face-to-face group sessions per calendar year) [ 35 ]. Some gamification elements and human-like characteristics were utilized in the MDC program design, as suggested by previous studies [ 36 ]. The recently published and separate evaluation from MDC users demonstrated that these techniques did increase users’ engagement with the program but were insufficient to ensure engagement among all users [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, age-related decline in cognitive flexibility, processing speed, and other cognitive functions in old age can make it challenging to adopt and manage these solutions well, which could mean a low adherence [ 63 ]. Other aspects to be carefully considered when developing mHealth solutions for the elderly are short-set ups and onboarding processes, and user-friendly and graphic visual cues facilitating the understandability of the mHealth solution [ 29 , 30 , 31 , 84 ]. Acceptance and usability requirements of the elderly diabetic patients were insufficiently considered despite these growing populations representing a large target group that could benefit from diabetes apps [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to acceptance and usability requirements for older adults with diabetes, this is especially relevant because, in this sample, several barriers could be found. For instance, the lack of technological skills [ 29 , 30 , 31 ], availability and access to the internet [ 32 ], differences in motivational aspects [ 33 ], and also functional and sensory limitations hampering the use of these technologies. A systematic review of all currently available diabetes apps for iOS and Android revealed that usability of diabetes apps for patients aged ≥50 was moderate to good when applied mainly to apps offering a small range of functions.…”
Section: Introductionmentioning
confidence: 99%
“… Acharya and Sarraf, 2017 , S. Adriaanse and Rensleigh, 2013 , Alawna et al, 2019 , Bert et al, 2014 , Botha et al, 2018 , Bradford, 1934 , Burke et al, 2011 , Cotton and Patel, 2019 , Direito et al, 2014 , de Abajo et al, 2011 , Edwards et al, 2016 , HRI, 2014 , Lister et al, 2014 , Lotka, 1926 , Moral-Munoz et al, 2018 , Priesterroth et al, 2019 , Price, 1963 , Rose et al, 2017 , Sullivan and Lachman, 2017 , West et al, 2012 .…”
Section: Uncited Referencesmentioning
confidence: 99%